Analisis Kinerja Kontraktor yang Menerapkan Sistem Manajemen Mutu ISO-9000 - Priyo, Mandiyo (Universitas Muhammadiyah Yogyakarta, 2009)
The growth in the implementation of quality management system standard as an instrument to win global market competition and to improve product and service quality has affected not only manufacturing industries but also construction industries. One of the standards that is most widely implemented by companies or organizations in quality management system may be the ISO 9000. It should be noted that the ISO 9000 is not a standard for products or services, but it is a standard for quality management system employed in their production process. The objective of this research is to study the implementation of the ISO 9000 standard by the PT. Wijaya Karya Beton that has adopted the ISO 9000 for its quality management system standard. In addition, the criteria for evaluating its performance have also been identified. This criterion includes written procedure and its consistent implementation, as well as the measurement of the implementation result of its operation process flow and working procedures. This research was carried out by means of performance measurement, i.e. qualitatively by employing questionnaire, scoring and measurement on productivity and targeted quality achievement such as rework rate and reject rate. The data were collected by observation, extraction from the internal and external quality audit report, as well as daily-, weekly- and monthly reports on the pile production. The effect of company’s performance that employs the ISO 9000 standard (qualitative measurement) on the productivity, rework rate and reject rate (quantitative measurement) were analysed using Pearson’s Product Moment correlation analysis technique. The result reveals that the qualitative measurement resulted in continuous performance improvement, so did the quantitative measurement. It showed that these two measurement methods tends to be in a good agreement. A general conclusion that can be drawn is that the ISO 9000 has been properly implemented in the PT. Wijaya Karya Beton.